2019
DOI: 10.1038/s41565-019-0562-3
|View full text |Cite
|
Sign up to set email alerts
|

Artificial phototropism for omnidirectional tracking and harvesting of light

Abstract: Many living organisms track light sources and halt their movement when alignment is achieved. This phenomenon, known as phototropism, occurs, for example, when plants self-orient to face the sun throughout the day. Although many artificial smart materials exhibit non-directional, nastic behaviour in response to an external stimulus, no synthetic material can intrinsically detect and accurately track the direction of the stimulus, that is, exhibit tropistic behaviour. Here we report an artificial phototropic sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
197
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(207 citation statements)
references
References 47 publications
3
197
0
Order By: Relevance
“…Very recently, Zhao et al reported a swimmer robot based on a photosensitive hydrogel oscillator showing negative phototactic movement (away from the light source) in water driven by a laser 4. They further developed an artificial phototropic system based on hydrogels or a series of photoresponsive polymers that can autonomously aim and align in the incident light direction in three dimensions 67. In addition, Martella et al reported light‐activated nonreciprocal motion in LCNs, which can be applicable in swimming devices.…”
Section: Resultsmentioning
confidence: 99%
“…Very recently, Zhao et al reported a swimmer robot based on a photosensitive hydrogel oscillator showing negative phototactic movement (away from the light source) in water driven by a laser 4. They further developed an artificial phototropic system based on hydrogels or a series of photoresponsive polymers that can autonomously aim and align in the incident light direction in three dimensions 67. In addition, Martella et al reported light‐activated nonreciprocal motion in LCNs, which can be applicable in swimming devices.…”
Section: Resultsmentioning
confidence: 99%
“…[7] Heliotropismlike actuators have been developed to achieve light tracking in artificial fiber arrays based on a feedback loop involving photothermal effects and the mechanical properties of the polymers employed. [8] A photo active light guiding actuator has been constructed to drive photo thermal deformations. [9] For photothermal actuation, a specific chromophore is often added to the system so that when illuminated with the proper wavelength, a mechanical response is generated.…”
Section: Introductionmentioning
confidence: 99%
“…[5] Recently, there is a growing interest in developing synthetic out-of-equilibrium systems to mimic biology. [6,7] Synthetic outof-equilibrium materials have been reported that employ light, [8][9][10][11] current, [12] or heat to fuel characteristic dissipative behavior. [13] Biological out-of-equilibrium systems ubiquitously use chemical fuels, such as ATP and GTP, to sustain the dissipative processes.…”
mentioning
confidence: 99%